Strengthening Coastal Planning How Coastal Regions Could Benefit from Louisiana's Planning and Analysis Framework - Groves, David G. (RAND Corporation, 2014)
This report highlights RAND's contributions to the Louisiana Coastal Protection and Restoration Authority's Master Plan. Its purpose is to help policymakers in other coastal regions understand the value of a solid technical foundation to support decisionmaking on strategies to reduce flood risk, rebuild or restore coastal environments, and increase the resilience of developed coastal regions.